EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO BERBASIS PROBLEM BASED LEARNING (PBL) TERHADAP PEMAHAMAN KONSEP MATEMATIS - Surta M.D Panggabean; Yohanes; Hidayati Rais (Mat-Edukasia, 2017)
This research is based on the understanding of mathematical concepts using cooperative model of the power of two type based on problem based learning (pbl) better than conventional learning. This research uses quantitative approach with experiment method. The population in this study is the students of class VIII SMP Negeri 11 Merangin which amounted to 90 people consisting of 3 classes. Sampling technique using simple random sampling technique. The selected sample is class IX A as experiment class and class IX C as control class. Technique of data collecting through comprehension test of mathematical concept in the form of essay matter with the number of five items on the subject of kesebangunan. The data analysis technique used to test the hypothesis is t-test, with its calculation assisted by SPSS program. From the analysis of the final test data in the experimental class using the cooperative learning model of the power of two type based on problem based learning, it is obtained on average 81.77 while the control class using conventional learning obtained an average of 67.77. Hypothesis test results obtained t count> ttable or 5.634> 1.671 then H1 accepted and H0 rejected. The conclusion of this research is the understanding of mathematical concepts using cooperative model of the power of two type based on problem based learning better than conventional learning on the material kesebangunan class students IX SMP Negeri 11 Merangin lesson year 2017/2018. Keywords: Cooperative Learning Model Type The Power Of Two Problem Based Learning (PBL) And Understanding Mathematical Concepts